Jabatan Kerja Raya Daerah Johor Bahru / Muhammad Naqib Rosle - Rosle, Muhammad Naqib (2015)
Industrial training is one of example of modem learning environment that have been implement to the student. Industrial training refer to one situation that deal with real work environment, technically and also practically. Student have been teach with theory at university level, which means involve in class, examination and also laboratory. All of this course session is about to gained knowledge. To produce an excellent student, theory and practically must come together. With the aid of industrial training, student will expose to the real construction environment and also real work environment. With the aid of knowledge during university stage, student can use and implement the knowledge during industrial training. Industrial training offer student to gain their knowledge about civil engineering. Theory and practically is a different things to deal with. With the combination of theory and practically, student will be able to absorb new knowledge that cannot be offer by theory. Besides, industrial training also offer student to feel the real experience that is very important to student. Experience is something that cannot be buy, but only can by go through with situation. Student can able to expose with construction activities and can learn how the building to be construct. Lastly, with the implementation of industrial training, student will be able to improve their communication skill with is very important. Student can learn how to communicate with workers, the proper way to start a conversation and proper way to ask someone help. All of this can be a good end result to student in order to prepare a student that fixed with intelligent, experience and also knowledge.